Molecular Characterization of Basal‐Like and Non‐Basal‐Like Triple‐Negative Breast Cancer. (12th February 2013) - Prat, Aleix; Adamo, Barbara; Cheang, Maggie C.U.; Anders, Carey K.; Carey, Lisa A.; Perou, Charles M.
Abstract : Learning Objectives: Contrast the definitions of TN and basal‐like. Describe the undistinguishable global gene expression patterns of non‐basal‐like TN tumors versus non‐TN tumors that are non‐basal‐like. Describe the relationship between TN heterogeneity and tumor heterogeneity plus microenvironmental heterogeneity. Triple‐negative (TN) and basal‐like (BL) breast cancer definitions have been used interchangeably to identify breast cancers that lack expression of the hormone receptors and overexpression and/or amplification of HER2. However, both classifications show substantial discordance rates when compared to each other. Here, we molecularly characterize TN tumors and BL tumors, comparing and contrasting the results in terms of common patterns and distinct patterns for each. In total, when testing 412 TN and 473 BL tumors, 21.4% and 31.5% were identified as non‐BL and non‐TN, respectively. TN tumors identified as luminal or HER2‐enriched (HER2E) showed undistinguishable overall gene expression profiles when compared versus luminal or HER2E tumors that were not TN. Similar findings were observed within BL tumors regardless of their TN status, which suggests that molecular subtype is preserved regardless of individual marker results. Interestingly, most TN tumors identified as HER2E showed low HER2 expression and lacked HER2 amplification, despite the similar overall gene expression profiles to HER2E tumors that were clinically HER2‐positive. Lastly, additional genomic classifications were examined within TN and BL cancers, most of which were highly concordant with tumor intrinsic subtype. These results suggest that future clinical trials focused on TN disease should consider stratifying patients based upon BL versus non‐BL gene expression profiles, which appears to be the main biological difference seen in patients with TN breast cancer. Abstract : Triple‐negative breast cancer is a broad and diverse category for which additional subclassifications are needed. Therefore, future clinical trials should stratify patients based on a tumor′s basal‐like versus non‐basal‐like gene expression profile, which appears to be the main biological difference seen within triple‐negative breast cancer.